2020
DOI: 10.1002/fsn3.1505
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of high‐quality concentrated fragrance flaxseed oil by steam explosion pretreatment technology

Abstract: In this study, flaxseed was pretreated by steam explosion technology and subsequently pressed to prepare flaxseed oil. GC, UPLC, HPLC, and GC-MS techniques were used to analyze the quality characteristics of the prepared flaxseed oil. These included the food safety risk indices, micronutrient components, and oxidative stability. The effects of different steam explosion pressures on the quality characteristics and relative volatile components of flaxseed oil were also investigated. The results revealed that ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 22 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…There are significant differences between MR and oven roasting (OR): the volatile compounds of camellia seed oil prepared by MR and OR are different [ 27 ] and the bioactive composition of orange seed oil pretreated by these two methods have differences [ 28 ]. In addition, steaming roasting (SR) is also the conventional processing pretreatment of flaxseed oil [ 29 ] and camellia seed oil [ 30 ]. The advantages of this pretreatment are preventing oil oxidation with an oxygen-free environment and enhancing thermal degradation by increasing heat transfer [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are significant differences between MR and oven roasting (OR): the volatile compounds of camellia seed oil prepared by MR and OR are different [ 27 ] and the bioactive composition of orange seed oil pretreated by these two methods have differences [ 28 ]. In addition, steaming roasting (SR) is also the conventional processing pretreatment of flaxseed oil [ 29 ] and camellia seed oil [ 30 ]. The advantages of this pretreatment are preventing oil oxidation with an oxygen-free environment and enhancing thermal degradation by increasing heat transfer [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the most important component of vegetable oil, lipids can be divided into eight categories according to their structure and biochemical properties, namely, fatty acid (FA), glycerolipids (GLs), glycerophospholipids (GPs), sphingolipids (SPs), saccharolipids (SLs), sterol lipids (STs), polyketides (PKs), and prenol lipids (PRs; Yu et al, 2020 ). Lipids play an important role in organism growth and development, energy storage, material transport, and the recognition and transduction of molecular signals (Belayneh et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Effective and e cient pretreatments of rapeseed (canola seed equivalent) have been shown to constitute vital and necessary steps in order to produce high-quality oil during oil extraction (Azadmard-Damirchi et al, 2010a). Hence, techniques, such as ultrasound (Jalili et al, 2018), microwave (Zheng et al, 2014a), pulsed electric elds (Zhang et al, 2017), roasting (Różańska et al, 2019) and steam explosion (Yu et al, 2020), have been reported as pretreatment methods. A number of studies investigated and documented the impact of heat processing on rapeseed to deactivate endogenous enzymes, improve cell wall permeability, enhance the release of bioactive components and improve the extraction of oil-soluble polyphenols in the oil, thus leading to the greater oxidative stability of the oil (Azadmard-Damirchi et al, 2010b.…”
Section: Introductionmentioning
confidence: 99%